(untitled) (Research, Society and Development, 2021)
Photodynamic therapy (PDT) is a promising therapeutic modality for treating cancer, including breast tumors. The oxidative damage caused by PDT culminates in cell death, induction of immune response, and the resulting destruction of the tumor. This study aimed to evaluate the gene expression profiling of genes BCL-2, BAX, and HER-2 and their proteins after PDT, associating it with the necrosis caused by this therapy under different fluences. Twenty-eight female rats received a single dose of 7,12-dimethylbenz (a) anthracene (DMBA - 80mg/kg), by gavage, for breast tumor induction. After the tumors grew, the animals were divided into four groups: G1 - control group – untreated breast tumor – and G2, G3, and G4 groups treated with PDT using Photogem@ as photosensitizer and interstitial irradiation, with fluences of 50J/cm, 100J/cm, and 150J/cm, respectively. Samples of tumors were harvested for histological examination by RT-qPCR. The RT-qPCR showed that the gene expression profiling of BCL-2, BAX, and HER-2 was not altered after PDT. Hemorrhagic necrosis and qualitatively greater vascular and cellular damage were observed and correlated positively with the fluence. PDT does not seem to induce the modulation of genes related to apoptosis. The results indicate that the type of cell death stimulated by PDT in breast tumor is necrosis.